Acid- and alkali-resistant emulsion thickener for anticorrosive coatings and preparation method thereof
By adding a acid -alkaline resistant agent to the thickener of the anticorrosive coatings and forming a stable polymer network, the problem of the thickener's failure in extreme acid -alkali environments is solved, and the stable thickening effect of coatings under different pH conditions is achieved. And good attachment performance.
Patent Information
- Application Number
- CN202411441361.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-16
AI Technical Summary
Existing anticorrosion coating thickeners are prone to failure in extreme acid and alkali environments, affecting the stability and protective performance of the coating.
Add a acid and alkali agent to the thickener, and through specific process steps, including aluminum silicate modification and polymerization reactions, a stable polymer network is formed to improve the acid and alkali resistance of the thickener.
Anti -anticorrosive coatings maintain the viscosity and attachment effects in extreme pH environments, and improve the stability and protective performance of the coating.
Smart Images

Figure CN118955817B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of emulsion thickeners and relates to an acid- and alkali-resistant emulsion thickener for anticorrosive coatings and a preparation method thereof. Background Art
[0002] Anti-corrosion coatings play a vital role in protecting metal and concrete structures from corrosive environments. Anti-corrosion coatings effectively isolate the contact of corrosive media by forming a protective barrier on the metal and concrete surfaces, preventing the penetration and erosion of corrosive substances such as moisture, salt, and chemicals. They play a key role in maintaining the physical integrity of metal and concrete structures, thereby ensuring the mechanical properties and overall safety of the structures. The application of anti-corrosion coatings is of great significance for extending the service life of these structures. In addition, the use of anti-corrosion coatings can significantly reduce the maintenance and replacement costs caused by corrosion, thereby saving a lot of labor and material costs, and the economic benefits are particularly significant.
[0003] Existing thickeners, such as polyacrylates and hydroxyethyl cellulose, perform well in neutral or slightly acidic or alkaline environments, but are prone to failure in extreme acidic or alkaline environments because their chemical structure is easily decomposed by acid or alkali, thus affecting the stability and protective performance of the coating. However, in some special high-acid or high-alkali environments, anti-corrosion coatings need to have special chemical stability to ensure their protective performance and service life. The thickening effect of some thickeners will be significantly reduced in extreme pH environments, limiting the application of these anti-corrosion coatings in acidic or alkaline environments. Therefore, selecting a thickener that can still maintain a stable thickening effect under extreme pH conditions is crucial to optimizing the application performance of anti-corrosion coatings. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an acid- and alkali-resistant emulsion thickener for anti-corrosion coatings and a preparation method thereof. By adding an acid- and alkali-resistant agent to the thickener, the anti-corrosion coating can still maintain its viscosity under extreme pH conditions and has a good adhesion effect on metal and concrete, thereby meeting the needs of actual production.
[0005] To achieve this object, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a method for preparing an acid- and alkali-resistant emulsion thickener for anticorrosive coatings, the method for preparing the emulsion thickener comprising:
[0007] Step S1, adding raw materials, mixing 300-360 parts by weight of deionized water and 8-15 parts by weight of acid and alkali resistant agent, starting a stirring device, adding emulsifier A and stirring to obtain a mixed solution A;
[0008] Step S2, emulsification pretreatment, heating the mixed solution A to a first temperature, adding 80-120 parts by weight of the associative monomer, and continuing to stir to obtain a mixed solution B;
[0009] Step S3, preparing an initiating solution, using 2-8 parts by weight of an initiator and 50-60 parts by weight of deionized water to prepare an initiating solution;
[0010] Step S4, emulsifying the main monomer, adding 200-250 parts by weight of methacrylic acid, 100-150 parts by weight of butyl acrylate, 50-100 parts by weight of vinyl acetate and emulsifier B to the mixed solution B in sequence, and then adding 1-6 parts by weight of an auxiliary agent, and stirring is maintained to obtain a precursor solution A;
[0011] Step S5, polymerization reaction, raising the temperature of the precursor solution A to the second temperature, adding the initiator droplets to the precursor solution A, and dropping the temperature below the third temperature after sufficient reaction to obtain the final product.
[0012] The present invention adds butyl acrylate and vinyl acetate to the thickener to achieve the following effects:
[0013] (1) Butyl acrylate contains long-chain alkyl (butyl) and ester groups. The butyl chain is relatively long and has a certain flexibility. The butyl chain provides the ability to rotate freely within the molecule, allowing the polymer chain to deform to a certain extent under the action of external force without breaking easily. In the polymer network, the long-chain alkyl part of the butyl acrylate monomer can increase the distance between polymer chains, making the polymer network more elastic and flexible, thereby improving the flexibility of the thickener. The ester group (-COO-) in butyl acrylate has a certain polarity and can interact with other polar molecules or surfaces to increase adhesion. In a multiphase system (such as an emulsion), the ester group can interact with the interface between the dispersed phase and the continuous phase, improving the adhesion of the polymer at the interface, thereby improving the stability of the thickener;
[0014] (2) Vinyl acetate is a vinyl monomer that contains an ester group (-OCOCH3). The ester group in the vinyl acetate polymer chain can provide flexibility within the molecule, allowing the polymer chain to deform to a certain extent under the action of external forces. The chain segments formed by vinyl acetate in the polymer network are relatively flexible, which increases the elasticity and flexibility of the overall polymer network. The ester group (-OCOCH3) in vinyl acetate has a certain polarity and can interact with other polar molecules or surfaces to increase adhesion. In a multiphase system, the ester group in the vinyl acetate polymer chain can improve the adhesion ability at the interface, thereby improving the stability of the thickener;
[0015] (3) The ester groups of butyl acrylate and vinyl acetate can form hydrogen bonds and dipole-dipole interactions with other polymer chains or emulsifier molecules to form a stable polymer network. These interactions can form physical cross-linking points at the molecular level, enhancing the stability and adhesion of the polymer network. The long chain structure of butyl acrylate and vinyl acetate provides a larger intermolecular space in the polymer network, reduces the close stacking between chains, and increases the elasticity and flexibility of the entire system. This structure forms a looser but more stable network structure in the polymer network, which helps to improve the thickening effect and stability of the thickener.
[0016] The present invention adds methoxy polyethylene glycol methacrylate and nonylphenol polyoxyethylene ether methacrylate to the thickener to achieve the following effects:
[0017] (1) Methoxypolyethylene glycol methacrylate contains hydrophilic polyethylene glycol (PEG) chains and polymerizable methacrylate groups. The PEG chain has strong hydrophilicity and can attract and bind a large number of water molecules, so that the water molecules in the emulsion system form a stable hydration reaction and form a good hydration shell in the water phase, preventing the aggregation and merging of oil droplets in the emulsion, thereby improving the stability of the emulsion. In addition, the PEG chain can form physical cross-linking points in the water phase. These physical cross-linking points interact through hydrogen bonds and van der Waals forces between the PEG chains to form a stable three-dimensional network structure, thereby improving the thickening effect.
[0018] (2) Nonylphenol polyoxyethylene ether methacrylate contains hydrophobic nonylphenol groups and hydrophilic polyoxyethylene (POE) chains. The nonylphenol groups provide hydrophobicity and the POE chains provide hydrophilicity. This amphiphilic structure can form surfactant molecules in the emulsion, reduce the surface tension of the oil-water interface, and improve the stability of the emulsion;
[0019] (3) In the water phase, the amphiphilic structure of nonylphenol polyoxyethylene ether methacrylate enables it to spontaneously form micro-micelles, which form a stable micelle structure in the water phase, further increasing the stability of the emulsion and enhancing the thickening effect through physical cross-linking. In addition, a stable interfacial layer can be formed at the oil-water interface to prevent the aggregation and merging of oil droplets, thereby improving the uniformity and durability of the emulsion.
[0020] As a preferred technical solution of the present invention, in step S1, the weight parts of the deionized water are 300-360 parts, for example, it can be 300 parts, 306 parts, 312 parts, 318 parts, 324 parts, 330 parts, 336 parts, 342 parts, 348 parts, 354 parts or 360 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] In some optional examples, the weight proportion of the acid and alkali resistant agent is 8-15 parts, for example, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] In some optional examples, the usage amount of the emulsifier A is 30-60% of the mass of the associative monomers, for example, it can be 30%, 33%, 36%, 39%, 42%, 45%, 48%, 51%, 54%, 57% or 60%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] In some optional examples, the stirring time is 60-90 min, for example, it can be 60 min, 63 min, 66 min, 69 min, 72 min, 75 min, 78 min, 81 min, 84 min, 87 min or 90 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] As a preferred technical solution of the present invention, in step S2, the first temperature is 40-50°C, for example, it can be 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] In some optional examples, the associative monomers are in an amount of 80-120 parts by weight, for example, 80, 84, 88, 92, 96, 100, 104, 108, 112, 116 or 120 parts by weight, but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] In some optional examples, the stirring time is 60-90 min, for example, it can be 60 min, 63 min, 66 min, 69 min, 72 min, 75 min, 78 min, 81 min, 84 min, 87 min or 90 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] As a preferred technical solution of the present invention, in step S3, the weight parts of the initiator are 2-8 parts, for example, it can be 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts or 8 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] In some optional examples, the weight parts of deionized water is 50-60 parts, for example, it can be 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts or 60 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] In some optional examples, the stirring speed is 350-450rpm, for example, it can be 350rpm, 360rpm, 370rpm, 380rpm, 390rpm, 400rpm, 410rpm, 420rpm, 430rpm, 440rpm or 450rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] In some optional examples, the stirring time is 60-90 min, for example, it can be 60 min, 63 min, 66 min, 69 min, 72 min, 75 min, 78 min, 81 min, 84 min, 87 min or 90 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] As a preferred technical solution of the present invention, in step S4, the weight parts of methacrylic acid is 200-250 parts, for example, it can be 200 parts, 205 parts, 210 parts, 215 parts, 220 parts, 225 parts, 230 parts, 235 parts, 240 parts, 245 parts or 250 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] In some optional examples, the weight proportion of the butyl acrylate is 100-150 parts, for example, 100 parts, 105 parts, 110 parts, 115 parts, 120 parts, 125 parts, 130 parts, 135 parts, 140 parts, 145 parts or 150 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] In some optional examples, the weight proportion of the vinyl acetate is 50-100 parts, for example, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, 95 parts or 100 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] In some optional examples, the usage amount of the emulsifier B is 10-30% of the mass of the associative monomers, for example, it can be 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28% or 30%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] In some optional examples, the weight portion of the auxiliary agent is 1-6 parts, for example, it can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts or 6 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] In some optional examples, the stirring time is 60-90 min, for example, it can be 60 min, 63 min, 66 min, 69 min, 72 min, 75 min, 78 min, 81 min, 84 min, 87 min or 90 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] As a preferred technical solution of the present invention, in step S5, the second temperature is 70-80°C, for example, it can be 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] In some optional examples, the dropping speed is 1-2 mL / min, for example, it can be 1.0 mL / min, 1.1 mL / min, 1.2 mL / min, 1.3 mL / min, 1.4 mL / min, 1.5 mL / min, 1.6 mL / min, 1.7 mL / min, 1.8 mL / min, 1.9 mL / min or 2.0 mL / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] In some optional examples, the reaction time is 3-4h, for example, it can be 3.0h, 3.1h, 3.2h, 3.3h, 3.4h, 3.5h, 3.6h, 3.7h, 3.8h, 3.9h or 4.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] As a preferred technical solution of the present invention, the present invention provides a method for preparing an acid- and alkali-resistant emulsion thickener for anti-corrosion coatings, wherein the preparation method of the acid- and alkali-resistant agent is:
[0041] Step I, pretreatment of aluminum silicate, placing 14-24 parts by weight of aluminum silicate in a ball mill, adding steel balls for thorough grinding, and taking out after grinding and spraying and washing with deionized water to obtain fine aluminum silicate powder;
[0042] Step II, aluminum silicate modification, 10-20 parts by weight of deionized water, 50-70 parts by weight of isopropyl alcohol and epoxy silane are added to the fine aluminum silicate powder and stirred evenly. After stirring, the mixture is transferred to an oven and heated to ensure that the mixture is completely dry;
[0043] Step III, curing treatment, heating in an oven for curing treatment, and naturally cooling the cured aluminum silicate to room temperature;
[0044] Step IV, ion exchange, mixing the modified aluminum silicate powder with ion exchange resin and mixing by ultrasonic vibration;
[0045] Step V, washing and drying, washing the ion-exchanged aluminum silicate powder with deionized water, and drying it in an oven to obtain an acid and alkali resistant agent.
[0046] The present invention first modifies aluminum silicate powder. Epoxy silane (3-epoxypropyltriethoxysilane, GPTMS) undergoes a hydrolysis reaction in the presence of water to generate an intermediate containing silanol groups. These silanol groups can further react with hydroxyl groups (-OH) on the surface of aluminum silicate to form silicon oxygen bonds (Si-O-Si) through a condensation reaction, and the epoxy silane is chemically bonded to the surface of the aluminum silicate. At the same time, the epoxy groups in the epoxy silane are still retained after the silane coupling reaction, and can further react with other functional groups, such as hydroxyl groups (-OH) and amino groups (-NH2) in the resin, to form a cross-linked structure. This reaction can further enhance the bonding strength and acid and alkali resistance of the modified aluminum silicate and the base material.
[0047] In the ion exchange process of the present invention, the reaction between epoxy silane and the resin can form a siloxane network on the surface thereof, and this network can significantly improve the acid and alkali resistance of aluminum silicate. The specific reasons are: (1) surface coverage and shielding effect. The formed siloxane network covers the surface of aluminum silicate, providing a physical shield to prevent acidic and alkaline media from directly contacting aluminum silicate; (2) enhanced chemical stability. The siloxane network itself has high chemical stability and strong tolerance to acidic and alkaline media, thereby improving the acid and alkali resistance of aluminum silicate; (3) improved interface compatibility. The reaction between epoxy silane and ion exchange resin can enhance the interface bonding force between aluminum silicate and organic resin, thereby improving the overall stability and durability of the composite material.
[0048] As a preferred technical solution of the present invention, in step I, the aluminum silicate is 14-24 parts by weight, for example, it can be 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] In some optional instances, the diameter of the steel ball is 4-6 mm, for example, 4.2 mm, 4.4 mm, 4.6 mm, 4.8 mm, 5.0 mm, 5.2 mm, 5.4 mm, 5.6 mm, 5.8 mm or 6.0 mm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] As a preferred technical solution of the present invention, in step II, the deionized water is 10-20 parts by weight, for example, it can be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] In some optional examples, the isopropanol is 50-70 parts by weight, for example, it can be 50 parts, 52 parts, 54 parts, 56 parts, 58 parts, 60 parts, 62 parts, 64 parts, 66 parts, 68 parts or 70 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] In some optional examples, the amount of epoxy silane used is 1-10% of the weight of aluminum silicate, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] In some optional examples, the stirring time is 30-60 min, for example, it can be 30 min, 33 min, 36 min, 39 min, 42 min, 45 min, 48 min, 51 min, 54 min, 57 min or 60 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] In some optional examples, the drying temperature is 60-80°C, for example, it can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] As a preferred technical solution of the present invention, in step III, the heating temperature is 100-150°C, for example, it can be 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C or 150°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] As a preferred technical solution of the present invention, in step IV, the power of the ultrasonic vibration is 2000~3000W, for example, it can be 2000 W, 2100 W, 2200 W, 2300 W, 2400 W, 2500 W, 2600 W, 2700 W, 2800 W, 2900 W or 3000 W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] In some optional instances, the frequency of the ultrasonic vibration is 60-80 kHz, for example, it may be 60 kHz, 62 kHz, 64 kHz, 66 kHz, 68 kHz, 70 kHz, 72 kHz, 74 kHz, 76 kHz, 78 kHz or 80 kHz, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] In some optional instances, the ultrasonic vibration time is 20-40 min, for example, it can be 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, 32 min, 34 min, 36 min, 38 min or 40 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] As a preferred technical solution of the present invention, in step V, the drying temperature is 50-70°C, for example, it can be 50°C, 52°C, 54°C, 56°C, 58°C, 60°C, 62°C, 64°C, 66°C, 68°C or 70°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0060] In a second aspect, the present invention provides an acid- and alkali-resistant emulsion thickener for anti-corrosion coatings prepared by the preparation method described in the first aspect.
[0061] In a third aspect, the present invention provides a method for preparing an anti-corrosion coating, which comprises the following components in parts by weight: 30-80 parts by weight of a film-forming substance, 10-35 parts by weight of an acid- and alkali-resistant emulsion thickener, 1-5 parts by weight of a pigment, 1-5 parts by weight of an auxiliary agent and 20-50 parts by weight of a solvent, which are mixed evenly.
[0062] As a preferred technical solution of the present invention, the weight parts of the film-forming substance can be 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts or 80 parts, the weight parts of the acid and alkali resistant emulsion thickener can be 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts or 25 parts, the weight parts of the pigment can be 1 part, 2 parts, 3 parts, 4 parts or 5 parts, the weight parts of the auxiliary agent can be 1 part, 2 parts, 3 parts, 4 parts or 5 parts, the weight parts of the solvent can be 20 parts, 23 parts, 26 parts, 29 parts, 32 parts, 35 parts, 38 parts, 41 parts, 44 parts, 47 parts or 50 parts, but are not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0063] Compared with the prior art, the present invention has the following beneficial effects:
[0064] (1) The present invention modifies aluminum silicate, and uses the intermediate containing silanol groups generated by the hydrolysis reaction of epoxy silane to react with the hydroxyl groups (-OH) on the surface of aluminum silicate, and the condensation reaction forms a silicon oxygen bond (Si-O-Si), thereby chemically bonding the epoxy silane to the surface of the aluminum silicate. At the same time, the epoxy group in the epoxy silane is still retained after the silane coupling reaction, and can further react with other functional groups, such as hydroxyl groups (-OH) and amino groups (-NH2) in the resin, to form a cross-linked structure, which can further enhance the bonding strength and acid and alkali resistance of the modified aluminum silicate to the matrix material. The modified aluminum silicate is incorporated into the preparation of the thickener, so that the thickening effect of the thickener on the article is little affected by the pH value, which effectively improves the stability of the thickener and ensures that the thickening effect of the thickener is not affected under different pH conditions;
[0065] (2) The ester groups of butyl acrylate and vinyl acetate in the present invention can form hydrogen bonds and dipole-dipole interactions with other polymer chains or emulsifier molecules to form a stable polymer network. These interactions can form physical crosslinking points at the molecular level, enhancing the stability and adhesion of the polymer network. The long chain structure of butyl acrylate and vinyl acetate provides a larger intermolecular space in the polymer network, reduces the tight stacking between chains, and increases the elasticity and flexibility of the entire system. This structure forms a looser but stable network structure in the polymer network, which helps to improve the thickening effect and stability of the thickener;
[0066] (3) The methoxy polyethylene glycol methacrylate in the present invention contains a hydrophilic polyethylene glycol (PEG) chain, which can attract and bind a large number of water molecules, so that the water molecules in the emulsion system form a stable hydration, form a good hydration shell in the water phase, and improve the stability of the emulsion. In addition, the PEG chain can form physical crosslinking points in the water phase. These physical crosslinking points interact through hydrogen bonds and van der Waals forces between the PEG chains to form a stable three-dimensional network structure, thereby improving the thickening effect. Nonylphenol polyoxyethylene ether methacrylate contains an amphiphilic structure, which enables it to spontaneously form micro-micelles. These micro-micelles form a stable micelle structure in the water phase, further increasing the stability of the emulsion, and enhancing the thickening effect through physical crosslinking. A stable interface layer can be formed at the oil-water interface, thereby improving the uniformity and durability of the emulsion. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Figure 1 A process flow chart of the preparation of an acid- and alkali-resistant emulsion thickener for anticorrosive coatings provided in Examples 1-6 of the present invention;
[0068] Figure 2 This is a SEM image of the aluminum silicate prepared in Example 1 of the present invention;
[0069] Figure 3 This is the TEM image of aluminum silicate prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0070] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.
[0071] The chemical reagents used in the examples and comparative examples of the present invention are all commercially available products, and their brands, specifications and manufacturer information are as follows:
[0072] Fatty alcohol polyoxyethylene ether, purity ≥99%, purchased from Shanghai Bangao Chemical Co., Ltd.;
[0073] Fatty alcohol polyoxyethylene ether sulfate sodium salt, purity ≥99%, purchased from Shandong Zibo Haijie Chemical Co., Ltd.;
[0074] Sodium lauryl polyoxyethylene ether sulfate, active matter content 70%, purchased from Shandong Tongfengqi Chemical Co., Ltd.;
[0075] Methoxy polyethylene glycol methacrylate, purity ≥99%, purchased from Liaoning Kelong Fine Chemical Co., Ltd.;
[0076] Nonylphenol polyoxyethylene ether methacrylate, purity ≥99%, purchased from Nanjing Xinlida Chemical Co., Ltd.;
[0077] 3-Epoxypropyltriethoxysilane. Purity ≥ 97%, purchased from Shandong Sike New Materials Co., Ltd.;
[0078] Other raw materials can be purchased from the market.
[0079] Example 1
[0080] This embodiment provides a method for preparing an acid- and alkali-resistant emulsion thickener for anticorrosive coatings, such as Figure 1 As shown, the preparation method specifically comprises the following steps:
[0081] Step I, aluminum silicate pretreatment, placing 18 g of aluminum silicate in a ball mill, adding steel balls for full grinding, taking out after grinding and spraying with deionized water to obtain fine aluminum silicate powder;
[0082] Step II, aluminum silicate modification, in container A, add 14 g of deionized water, 67 g of isopropanol and 0.9 g of epoxy silane to the fine aluminum silicate powder and stir for 40 min. After stirring, transfer the mixture to an oven and heat at 71 ° C to ensure that the mixture is completely dry;
[0083] Step III, curing treatment, heating in an oven at 135° C. for curing treatment, and the aluminum silicate after curing treatment is naturally cooled to room temperature;
[0084] Step IV, ion exchange, mixing the modified aluminum silicate powder with ion exchange resin and mixing by ultrasonic vibration;
[0085] Step V, washing and drying, washing the ion-exchanged aluminum silicate powder with deionized water, and drying it in an oven to obtain an acid and alkali resistant agent;
[0086] Step S1, adding raw materials, mixing 320g of deionized water with 9g of acid and alkali resistant agent, starting a stirring device, adding 36g of fatty alcohol polyoxyethylene ether sulfate sodium salt and stirring for 65min to obtain a mixed solution A;
[0087] Step S2, emulsification pretreatment, heating the reactor to 45° C., adding 90 g of methoxy polyethylene glycol methacrylate, and continuing stirring for 72 min to obtain a mixed solution B;
[0088] Step S3, preparation of an initiating solution, using 4 g of ammonium persulfate and 54 g of deionized water to prepare an initiating solution;
[0089] Step S4, emulsifying the main monomer, adding 230g of methacrylic acid, 126g of butyl acrylate, 80g of vinyl acetate and 18g of sodium lauryl alcohol polyoxyethylene ether sulfate to the reaction kettle in sequence, and then adding 3g of disodium ethylenediaminetetraacetate, and stirring to obtain a precursor solution A;
[0090] Step S5, polymerization reaction, raising the temperature of the precursor solution A to 75°C, slowly adding the initiator solution to the precursor solution A at a rate of 1.3 mL / min, and allowing the temperature to drop below 40°C after sufficient reaction for 3.5 hours to obtain the final product.
[0091] The present embodiment also provides an anti-corrosion coating, including a film-forming substance, an acid- and alkali-resistant thickener, a pigment, an additive and a solvent, and the preparation method thereof is as follows: 47 g of a film-forming substance, 17 g of an acid- and alkali-resistant thickener, 2 g of a pigment, 3 g of an additive and 30 g of a solvent are mixed evenly to obtain an anti-corrosion coating.
[0092] Figure 2 and Figure 3 The SEM and TEM images of the modified aluminum silicate prepared in Example 1 show that the size of the material is 100 nm.
[0093] Example 2
[0094] This embodiment provides a method for preparing an acid- and alkali-resistant emulsion thickener for anticorrosive coatings, such as Figure 1 As shown, the preparation method specifically comprises the following steps:
[0095] Step I, aluminum silicate pretreatment, placing 16 g of aluminum silicate in a ball mill, adding steel balls for full grinding, taking out after grinding and spraying and washing with deionized water to obtain fine aluminum silicate powder;
[0096] Step II, aluminum silicate modification, in container A, add 18 g of deionized water, 55 g of isopropyl alcohol and 1.12 g of epoxy silane to the fine aluminum silicate powder and stir for 52 min. After stirring, transfer the mixture to an oven and heat at 66 ° C to ensure that the mixture is completely dry;
[0097] Step III, curing treatment, heating in an oven at 132° C. for curing treatment, and the aluminum silicate after curing treatment is naturally cooled to room temperature;
[0098] Step IV, ion exchange, mixing the modified aluminum silicate powder with ion exchange resin and mixing by ultrasonic vibration;
[0099] Step V, washing and drying, washing the ion-exchanged aluminum silicate powder with deionized water, and drying it in an oven to obtain an acid and alkali resistant agent;
[0100] Step S1, adding raw materials, mixing 330g of deionized water with 13g of acid and alkali resistant agent, starting a stirring device, adding 44g of fatty alcohol polyoxyethylene ether and stirring for 80min to obtain a mixed solution A;
[0101] Step S2, emulsification pretreatment, heating the reactor to 48° C., adding 110 g of methoxy polyethylene glycol methacrylate, and continuing stirring for 70 min to obtain a mixed solution B;
[0102] Step S3, preparation of an initiating solution, using 6 g of sodium persulfite and 60 g of deionized water to prepare an initiating solution;
[0103] Step S4, emulsifying the main monomer, adding 220g of methacrylic acid, 130g of butyl acrylate, 65g of vinyl acetate and 11g of sodium lauryl polyoxyethylene ether sulfate to the reaction kettle in sequence, and then adding 4g of trisodium phosphate, and keeping stirring to obtain a precursor solution A;
[0104] Step S5, polymerization reaction, raising the temperature of the precursor solution A to 73°C, slowly adding the initiator solution to the precursor solution A at a rate of 1.6 mL / min, and allowing the temperature to drop below 40°C after sufficient reaction for 3.3 hours to obtain the final product.
[0105] The present embodiment also provides an anti-corrosion coating, including a film-forming substance, an acid- and alkali-resistant thickener, a pigment, an additive and a solvent, and the preparation method thereof is as follows: 56 g of film-forming substance, 20 g of acid- and alkali-resistant thickener, 3 g of pigment, 4 g of additive and 27 g of solvent are mixed evenly to obtain the anti-corrosion coating.
[0106] Example 3
[0107] This embodiment provides a method for preparing an acid- and alkali-resistant emulsion thickener for anticorrosive coatings, such as Figure 1 As shown, the preparation method specifically comprises the following steps:
[0108] Step I, aluminum silicate pretreatment, 21g of aluminum silicate is placed in a ball mill, steel balls are added for full grinding, and after grinding, it is taken out and sprayed with deionized water for washing to obtain fine aluminum silicate powder;
[0109] Step II, aluminum silicate modification, in container A, 13 g of deionized water, 50 g of isopropanol and 0.63 g of epoxy silane were added to the fine aluminum silicate powder and stirred for 49 min. After the stirring was completed, the mixture was transferred to an oven and heated at 77 ° C to ensure that the mixture was completely dry;
[0110] Step III, curing treatment, heating in an oven at 118°C for curing treatment, and the aluminum silicate after curing treatment is naturally cooled to room temperature;
[0111] Step IV, ion exchange, mixing the modified aluminum silicate powder with ion exchange resin and mixing by ultrasonic vibration;
[0112] Step V, washing and drying, washing the ion-exchanged aluminum silicate powder with deionized water, and drying it in an oven to obtain an acid and alkali resistant agent;
[0113] Step S1, adding raw materials, mixing 350g of deionized water with 15g of acid and alkali resistant agent, starting a stirring device, adding 38g of fatty alcohol polyoxyethylene ether sulfate sodium salt and stirring for 70min to obtain a mixed solution A;
[0114] Step S2, emulsification pretreatment, heating the reactor to 50° C., adding 100 g of methoxy polyethylene glycol methacrylate, and continuing stirring for 78 min to obtain a mixed solution B;
[0115] Step S3, preparation of an initiating solution, using 5 g of ammonium persulfate and 57 g of deionized water to prepare an initiating solution;
[0116] Step S4, emulsifying the main monomer, adding 218g of methacrylic acid, 126g of butyl acrylate, 79g of vinyl acetate and 19g of sodium lauryl polyoxyethylene ether sulfate to the reaction kettle in sequence, and then adding 5g of trisodium phosphate, and stirring is maintained to obtain a precursor solution A;
[0117] Step S5, polymerization reaction, raising the temperature of the precursor solution A to 76°C, slowly adding the initiator solution to the precursor solution A at a rate of 1.8 mL / min, and allowing the temperature to drop below 40°C after sufficient reaction for 3.7 hours to obtain the final product.
[0118] The present embodiment also provides an anti-corrosion coating, including a film-forming substance, an acid- and alkali-resistant thickener, a pigment, an additive and a solvent, and the preparation method thereof is as follows: 49 g of film-forming substance, 22 g of acid- and alkali-resistant thickener, 2 g of pigment, 3 g of additive and 36 g of solvent are mixed evenly to obtain the anti-corrosion coating.
[0119] Example 4
[0120] This embodiment provides a method for preparing an acid- and alkali-resistant emulsion thickener for anticorrosive coatings, such as Figure 1 As shown, the preparation method specifically comprises the following steps:
[0121] Step I, aluminum silicate pretreatment, 21g of aluminum silicate is placed in a ball mill, steel balls are added for full grinding, and after grinding, it is taken out and sprayed with deionized water for washing to obtain fine aluminum silicate powder;
[0122] Step II, aluminum silicate modification, in container A, add 17 g of deionized water, 70 g of isopropanol and 1.68 g of epoxy silane to the fine aluminum silicate powder and stir for 43 min. After stirring, transfer the mixture to an oven and heat at 70 ° C to ensure that the mixture is completely dry;
[0123] Step III, curing treatment, heating in an oven at 129° C. for curing treatment, and the aluminum silicate after curing treatment is naturally cooled to room temperature;
[0124] Step IV, ion exchange, mixing the modified aluminum silicate powder with ion exchange resin and mixing by ultrasonic vibration;
[0125] Step V, washing and drying, washing the ion-exchanged aluminum silicate powder with deionized water, and drying it in an oven to obtain an acid and alkali resistant agent;
[0126] Step S1, adding raw materials, mixing 339g of deionized water with 11g of acid and alkali resistant agent, starting a stirring device, adding 40g of fatty alcohol polyoxyethylene ether sulfate sodium salt and stirring for 64min to obtain a mixed solution A;
[0127] Step S2, emulsification pretreatment, heating the reactor to 44° C., adding 108 g of methoxy polyethylene glycol methacrylate, and continuing stirring for 68 min to obtain a mixed solution B;
[0128] Step S3, preparation of an initiating solution, using 3 g of sodium persulfite and 50 g of deionized water to prepare an initiating solution;
[0129] Step S4, emulsifying the main monomer, adding 233g of methacrylic acid, 131g of butyl acrylate, 79g of vinyl acetate and 16g of sodium lauryl polyoxyethylene ether sulfate to the reaction kettle in sequence, and then adding 2g of disodium ethylenediaminetetraacetate, and stirring to obtain a precursor solution A;
[0130] Step S5, polymerization reaction, raising the temperature of the precursor solution A to 80°C, slowly adding the initiator solution A to the precursor solution A at a rate of 1.7 mL / min, and after fully reacting for 3.9 hours, the temperature dropped to below 40°C to obtain the final product.
[0131] The present embodiment also provides an anti-corrosion coating, including a film-forming substance, an acid- and alkali-resistant thickener, a pigment, an additive and a solvent, and the preparation method thereof is as follows: 61 g of film-forming substance, 19 g of acid- and alkali-resistant thickener, 3 g of pigment, 3 g of additive and 31 g of solvent are mixed evenly to obtain the anti-corrosion coating.
[0132] Example 5
[0133] This embodiment provides a method for preparing an acid- and alkali-resistant emulsion thickener for anticorrosive coatings, such as Figure 1As shown, the preparation method specifically comprises the following steps:
[0134] Step I, aluminum silicate pretreatment, placing 14 g of aluminum silicate in a ball mill, adding steel balls for full grinding, taking out after grinding and spraying and washing with deionized water to obtain fine aluminum silicate powder;
[0135] Step II, aluminum silicate modification, in container A, add 20 g of deionized water, 70 g of isopropanol and 0.56 g of epoxy silane to the fine aluminum silicate powder and stir for 40 min. After stirring, transfer the mixture to an oven and heat at 80°C to ensure that the mixture is completely dry;
[0136] Step III, curing treatment, heating in an oven at 147°C for curing treatment, and the aluminum silicate after curing treatment is naturally cooled to room temperature;
[0137] Step IV, ion exchange, mixing the modified aluminum silicate powder with ion exchange resin and mixing by ultrasonic vibration;
[0138] Step V, washing and drying, washing the ion-exchanged aluminum silicate powder with deionized water, and drying it in an oven to obtain an acid and alkali resistant agent;
[0139] Step S1, adding raw materials, adding 324g of deionized water and 10g of acid and alkali resistance agent into the reactor, starting the stirring device, adding 37g of fatty alcohol polyoxyethylene ether sulfate sodium salt and stirring for 79min to obtain a mixed solution A;
[0140] Step S2, emulsification pretreatment, heating the reactor to 43° C., adding 98 g of nonylphenol polyoxyethylene ether methacrylate, and continuing stirring for 80 min to obtain a mixed solution B;
[0141] Step S3, preparation of an initiating solution, using 7 g of sodium persulfite and 60 g of deionized water to prepare an initiating solution;
[0142] Step S4, emulsifying the main monomer, adding 241g of methacrylic acid, 119g of butyl acrylate, 68g of vinyl acetate and 21g of sodium lauryl polyoxyethylene ether sulfate to the reaction kettle in sequence, and then adding 3g of disodium ethylenediaminetetraacetate, and stirring to obtain a precursor solution A;
[0143] Step S5, polymerization reaction, raising the temperature of the precursor solution A to 76°C, slowly adding the initiator solution to the precursor solution A at a rate of 1.9 mL / min, and allowing the temperature to drop below 40°C after sufficient reaction for 3.3 hours to obtain the final product.
[0144] The present embodiment also provides an anti-corrosion coating, including a film-forming substance, an acid- and alkali-resistant thickener, a pigment, an additive and a solvent, and the preparation method thereof is as follows: 47 g of film-forming substance, 16 g of acid- and alkali-resistant thickener, 3 g of pigment, 4 g of additive and 44 g of solvent are mixed evenly to obtain the anti-corrosion coating.
[0145] Example 6
[0146] This embodiment provides a method for preparing an acid- and alkali-resistant emulsion thickener for anticorrosive coatings, such as Figure 1 As shown, the preparation method specifically comprises the following steps:
[0147] Step I, aluminum silicate pretreatment, placing 16 g of aluminum silicate in a ball mill, adding steel balls for full grinding, taking out after grinding and spraying and washing with deionized water to obtain fine aluminum silicate powder;
[0148] Step II, aluminum silicate modification, in container A, add 18 g of deionized water, 55 g of isopropanol and 0.48 g of epoxy silane to the fine aluminum silicate powder and stir for 52 min. After stirring, transfer the mixture to an oven and heat at 66 ° C to ensure that the mixture is completely dry;
[0149] Step III, curing treatment, heating in an oven at 132° C. for curing treatment, and the aluminum silicate after curing treatment is naturally cooled to room temperature;
[0150] Step IV, ion exchange, mixing the modified aluminum silicate powder with ion exchange resin and mixing by ultrasonic vibration;
[0151] Step V, washing and drying, washing the ion-exchanged aluminum silicate powder with deionized water, and drying it in an oven to obtain an acid and alkali resistant agent;
[0152] Step S1, adding raw materials, adding 317g of deionized water and 9g of acid and alkali resistant agent into the reactor, starting the stirring device, adding 35g of fatty alcohol polyoxyethylene ether sulfate sodium salt and stirring for 86min to obtain a mixed solution A;
[0153] Step S2, emulsification pretreatment, heating the reactor to 48° C., adding 96 g of methoxy polyethylene glycol methacrylate, and continuing stirring for 76 min to obtain a mixed solution B;
[0154] Step S3, preparation of an initiating solution, using 5 g of ammonium persulfate and 57 g of deionized water to prepare an initiating solution;
[0155] Step S4, emulsifying the main monomer, adding 226g of methacrylic acid, 128g of butyl acrylate, 72g of vinyl acetate and 12g of sodium lauryl polyoxyethylene ether sulfate to the reaction kettle in sequence, and then adding 2g of disodium ethylenediaminetetraacetate, and stirring to obtain a precursor solution A;
[0156] Step S5, polymerization reaction, raising the temperature of the precursor solution A to 72°C, slowly adding the initiator solution to the precursor solution A at a rate of 1.4 mL / min, and allowing the temperature to drop below 40°C after sufficient reaction for 3.9 hours to obtain the final product.
[0157] The present embodiment also provides an anti-corrosion coating, including a film-forming substance, an acid- and alkali-resistant thickener, a pigment, an additive and a solvent, and the preparation method thereof is as follows: 51 g of film-forming substance, 22 g of acid- and alkali-resistant thickener, 4 g of pigment, 2 g of additive and 34 g of solvent are mixed evenly to obtain the anti-corrosion coating.
[0158] Comparative Example 1
[0159] The present embodiment provides a method for preparing an acid- and alkali-resistant emulsion thickener for anti-corrosion coatings. The difference from Example 1 is that in step S1, the mass of fatty alcohol polyoxyethylene ether sodium sulfate is adjusted to 20 parts by weight. Compared with Example 1, the mass of fatty alcohol polyoxyethylene ether sodium sulfate in the present embodiment is reduced by 16 parts, and the reduced 16 parts are added in equal proportion to the mass of deionized water, acid and alkali resistant agent, methoxy polyethylene glycol methacrylate, ammonium persulfate, methacrylic acid, butyl acrylate, vinyl acetate, sodium lauryl alcohol polyoxyethylene ether sulfate, and disodium ethylenediaminetetraacetic acid, so that the mass ratios of the other components except the fatty alcohol polyoxyethylene ether sodium sulfate remain unchanged, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0160] Comparative Example 2
[0161] The present embodiment provides a method for preparing an acid- and alkali-resistant emulsion thickener for anti-corrosion coatings. The difference from Example 1 is that in step S1, the mass of fatty alcohol polyoxyethylene ether sodium sulfate is adjusted to 60 parts by weight. Compared with Example 1, the mass of fatty alcohol polyoxyethylene ether sodium sulfate in the present embodiment is increased by 24 parts, and the increased 24 parts are deducted from the mass of deionized water, acid and alkali resistant agent, methoxy polyethylene glycol methacrylate, ammonium persulfate, methacrylic acid, butyl acrylate, vinyl acetate, sodium lauryl polyoxyethylene ether sulfate, and disodium ethylenediaminetetraacetic acid in equal proportions, so that the mass ratios of other components except fatty alcohol polyoxyethylene ether sodium sulfate remain unchanged, and other process parameters and operating steps are exactly the same as those in Example 1.
[0162] Comparative Example 3
[0163] The present embodiment provides a method for preparing an acid- and alkali-resistant emulsion thickener for anti-corrosion coatings. The difference from the embodiment 1 is that in step S4, the mass of methacrylic acid is adjusted to 180 parts by weight. Compared with the embodiment 1, the mass of methacrylic acid in the present embodiment is reduced by 50 parts, and the reduced 50 parts are added in equal proportion to the mass of deionized water, acid and alkali-resistant agent, sodium salt of fatty alcohol polyoxyethylene ether sulfate, methoxy polyethylene glycol methacrylate, ammonium persulfate, butyl acrylate, vinyl acetate, sodium lauryl alcohol polyoxyethylene ether sulfate, and disodium ethylenediaminetetraacetic acid, so that the mass ratios of the other components except methacrylic acid remain unchanged, and the other process parameters and operation steps are exactly the same as those in the embodiment 1.
[0164] Comparative Example 4
[0165] The present embodiment provides a method for preparing an acid- and alkali-resistant emulsion thickener for anti-corrosion coatings. The difference from the embodiment 1 is that in step S4, the mass of methacrylic acid is adjusted to 270 parts by weight. Compared with the embodiment 1, the mass of methacrylic acid in the present embodiment is increased by 40 parts by weight, and the increased 40 parts are deducted from the mass of deionized water, acid and alkali-resistant agent, sodium salt of fatty alcohol polyoxyethylene ether sulfate, methoxy polyethylene glycol methacrylate, ammonium persulfate, butyl acrylate, vinyl acetate, sodium lauryl polyoxyethylene ether sulfate, and disodium ethylenediaminetetraacetic acid in proportion, so that the mass ratios of the other components except methacrylic acid remain unchanged, and the other process parameters and operation steps are exactly the same as those in the embodiment 1.
[0166] The viscosities of Examples 1-6 and Comparative Examples 1-4 were tested respectively according to the national standard GB / T 9269-2009.
[0167] It can be seen from the data in Table 1 that the viscosity of the anti-corrosion coatings prepared in Examples 1-6 at different pH values is higher than that of Comparative Examples 1-4, which indicates that the anti-corrosion coatings prepared by the preparation method provided by the present invention have excellent acid and alkali resistance.
[0168] Table 1 Test data of anti-corrosion coating viscosity
[0169]
[0170] It can be seen from the test data of Example 1, Comparative Example 1 and Comparative Example 2 that the viscosity of the anticorrosive coatings of Comparative Example 1 and Comparative Example 2 is lower than that of Example 1 at different pH values, which indicates that the acid and alkali resistance of the anticorrosive coatings prepared in Comparative Example 1 and Comparative Example 2 is inferior to that of Example 1. This is because the content of the sodium salt of fatty alcohol polyoxyethylene ether sulfate emulsifier in Comparative Example 1 is too low, resulting in the inability to completely coat the oil droplets, the oil droplets are easily aggregated and merged, the oil-water interface cannot be effectively stabilized, the dispersion effect of the oil phase and the water phase is not good, resulting in uneven viscosity, affecting the overall thickening effect of the thickener; while the content of sodium salt of fatty alcohol polyoxyethylene ether sulfate in Comparative Example 2 is too high, free micelles will be formed in the emulsion, and these micelles cannot effectively participate in the structural construction of the thickener, resulting in reduced viscosity. It makes it difficult to form a polymer network, affecting the performance of the acid and alkali resistant emulsion thickener, and further affecting the acid and alkali resistance of the anticorrosive coating finally prepared.
[0171] It can be seen from the test data of Example 1, Comparative Example 3 and Comparative Example 4 that the viscosity of the anticorrosive coatings of Comparative Example 3 and Comparative Example 4 is lower than that of Example 1 at different pH values, which indicates that the acid and alkali resistance of the anticorrosive coatings prepared in Comparative Example 3 and Comparative Example 4 is inferior to that of Example 1. This is because the content of the main monomer methacrylic acid in Comparative Example 3 is too low, which will reduce the polar molecules in the system, thereby reducing the hydrogen bonding force with water, reducing the crosslinking points in the polymer, resulting in a decrease in the crosslinking density of the polymer and insufficient adhesion; while the content of methacrylic acid in Comparative Example 4 is too high, and the polarity and acidity of methacrylic acid are relatively strong. Excessive methacrylic acid will make the hydrophilicity of the polymer too strong, resulting in poor solubility in organic solvents, affecting the dispersibility and uniformity of the product, affecting the performance of the acid and alkali resistant emulsion thickener, and further affecting the acid and alkali resistance of the anticorrosive coating finally prepared.
[0172] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing an acid- and alkali-resistant emulsion thickener for anticorrosive coatings, characterized in that: The preparation method comprises: Step S1, adding raw materials, mixing 300-360 parts by weight of deionized water and 8-15 parts by weight of acid and alkali resistant agent, starting a stirring device, adding emulsifier A and stirring to obtain a mixed solution A; Step S2, emulsification pretreatment, heating the mixed solution A to a first temperature, adding 80-120 parts by weight of the associative monomer, and continuing to stir to obtain a mixed solution B; Step S3, preparing an initiating solution, using 2-8 parts by weight of an initiator and 50-60 parts by weight of deionized water to prepare an initiating solution; Step S4, emulsifying the main monomer, adding 200-250 parts by weight of methacrylic acid, 100-150 parts by weight of butyl acrylate, 50-100 parts by weight of vinyl acetate and emulsifier B to the mixed solution B in sequence, and then adding 1-6 parts by weight of an auxiliary agent, and stirring is maintained to obtain a precursor solution A; Step S5, polymerization reaction, raising the temperature of the precursor solution A to the second temperature, adding the initiator droplets to the precursor solution A, and dropping the temperature below the third temperature after sufficient reaction to obtain the final product; In step S1, the emulsifier A is one or more of fatty alcohol polyoxyethylene ether and fatty alcohol polyoxyethylene ether sodium sulfate emulsifier; the usage amount of the emulsifier A is 30-60% of the mass of the associative monomer; after adding the emulsifier A, the stirring time is 60-90 minutes; In step S2, the first temperature is 40-50° C.; the stirring time is 60-90 min; the associative monomer is methoxy polyethylene glycol methacrylate, nonylphenol polyoxyethylene ether methacrylate or a mixture thereof; The preparation method of the acid and alkali resistant agent is: Step I, pretreatment of aluminum silicate, placing 14-24 parts by weight of aluminum silicate in a ball mill, adding steel balls for thorough grinding, and taking out after grinding and spraying and washing with deionized water to obtain fine aluminum silicate powder; Step II, aluminum silicate modification, 10-20 parts by weight of deionized water, 50-70 parts by weight of isopropyl alcohol and epoxy silane are added to the fine aluminum silicate powder and stirred evenly. After stirring, the mixture is transferred to an oven and heated to ensure that the mixture is completely dry; Step III, curing treatment, heating in an oven for curing treatment, and naturally cooling the cured aluminum silicate to room temperature; Step IV, ion exchange, mixing the modified aluminum silicate powder with ion exchange resin and mixing by ultrasonic vibration; Step V, washing and drying, washing the ion-exchanged aluminum silicate powder with deionized water, and drying it in an oven to obtain an acid and alkali resistant agent.
2. The method for preparing an acid- and alkali-resistant emulsion thickener for anticorrosive coatings according to claim 1, characterized in that: In step S3, the initiator is one of sodium persulfite and ammonium persulfate or a mixture of the two; the initiator solution is prepared by dissolving the initiator in water and stirring the solution on a magnetic stirrer at a speed of 350-450 rpm for 60-90 min.
3. The method for preparing an acid- and alkali-resistant emulsion thickener for anticorrosive coatings according to claim 1, characterized in that: In step S4, the emulsifier B is sodium lauryl alcohol polyoxyethylene ether sulfate; the amount of the emulsifier B used is 10-30% of the mass of the associative monomer; the auxiliary agent is trisodium phosphate, disodium ethylenediaminetetraacetic acid or a mixture thereof; the stirring time is 60-90 minutes; In step S5, the second temperature is 70-80°C; the dropping speed is 1-2 mL / min; the reaction time is 3-4 h; and the third temperature is 40°C.
4. The method for preparing an acid- and alkali-resistant emulsion thickener for anticorrosive coatings according to claim 1, characterized in that: In step I, the diameter of the steel ball is 4-6 mm; In step II, the epoxy silane is 3-epoxypropyltriethoxysilane; the amount of the epoxy silane is 1-10% of the weight of the aluminum silicate; the stirring time is 30-60 minutes; the drying temperature is 60-80°C; In step III, the heating temperature is 100-150°C; In step IV, the power of the ultrasonic vibration is 2000-3000W; The frequency of the ultrasonic vibration is 60~80kHz; The ultrasonic vibration time is 20-40min; In step V, the drying temperature is 50-70°C.
5. An acid- and alkali-resistant emulsion thickener for anticorrosive coatings prepared by the preparation method according to any one of claims 1 to 4.
6. An anti-corrosion coating, characterized in that: The anticorrosive coating comprises the following components in parts by weight: 30-80 parts by weight of a film-forming substance, 10-35 parts by weight of the acid-base resistant emulsion thickener according to claim 5, 1-5 parts by weight of a pigment, 1-5 parts by weight of an auxiliary agent and 20-50 parts by weight of a solvent, which are mixed evenly.
7. The anticorrosive coating according to claim 6, characterized in that: The film-forming substance is one or a combination of two of phenolic resin, epoxy resin or chlorinated polyethylene; The pigment is rutile titanium dioxide.
8. The anticorrosive coating according to claim 6, characterized in that: The auxiliary agents are anti-sagging agent, dispersant, leveling agent and defoaming agent, and the mass ratio of the anti-sagging agent, dispersant, leveling agent and defoaming agent is 5:3:1.5:0.5; The solvent is one of benzene, xylene or butanol.
9. The anticorrosive coating according to claim 8, characterized in that: The anti-sagging agent is one or more combinations of bentonite, montmorillonite or kaolin.
Citation Information
Patent Citations
Epoxy silane oligomer and coating composition containing same
CN101189281A
Freezing-resistant acrylate suspended thickening emulsion and preparation method thereof
CN103772625A
Acid-alkali-resistant composite silicate thermal-insulation coating
CN107722756A